2012
DOI: 10.1007/s00705-012-1555-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel E6-E7 sequence variants of human papillomavirus 16

Abstract: The rate of evolution of the human papillomavirus 16 (HPV16) genome is low. However, the ability of the E6 oncoprotein to interact with distinct p53 variants causes selective pressure on the E6 gene. In addition, intratypic recombination events in the HPV16 E6 and E7 genes have been characterized as extraordinary phenomena during the evolutionary history of virus. In the present study, we identified two new sequence variants through nucleotide analysis of the E6-E7 region of the HPV16 genome. Maximum-likelihoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In 2014, Tsakogiannis et al . reported that the A1668G (A268A), G2073A (K403K), T2169C (D435D), T2189C (I442T), A2453T (N530I), C2454T (N530N), A2587T (R575W) and G2650A (E596K) mutations of HPV16 E1 were identified only in high-grade dysplasia cases in a Greek population 18. In the current study, we also found that A1668G (A268A) and G2650A (E596K) occurred only in the case group, and this finding suggested these two mutations may play key roles in the carcinogenesis of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Tsakogiannis et al . reported that the A1668G (A268A), G2073A (K403K), T2169C (D435D), T2189C (I442T), A2453T (N530I), C2454T (N530N), A2587T (R575W) and G2650A (E596K) mutations of HPV16 E1 were identified only in high-grade dysplasia cases in a Greek population 18. In the current study, we also found that A1668G (A268A) and G2650A (E596K) occurred only in the case group, and this finding suggested these two mutations may play key roles in the carcinogenesis of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the distribution of HPV16 variants is different in different regions and ethnicities 18-21. For example, the A1-A3 (European, EUR) is the predominant variant in the Greek population 18-20, but the A4 (Asian, As) is the predominant variant in the Han Chinese population 21. Thus, in the present study, we aimed to identify HPV16 E1 mutations in HPV16-positive asymptomatic individuals and HPV16-positive cervical cancer patients and then to evaluate the association of HPV16 E1 mutations with cervical cancer in a Han Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the E7 variants have been studied to a lesser extent than the E6 variants. Some studies have reported, based on the conserved regions (CR) 1, CR2, and CR3 of E7, 4 variants in the CR1 domain [94,95], 5 in CR2 [94,[96][97][98][99], and 14 in CR3 [94,95,[100][101][102][103]. The most frequent variant, up to 70% in the Asian population, is the E7-G647 variant located in the CR2 domain [88,94].…”
Section: Variants Of Hpv 16mentioning
confidence: 99%
“…The HPVs that infect the mucosal epithelium are classified into the genus Alphapapillomaviruses (alpha-HPVs), and according to their tumourigenic capacity they are subdivided into high-risk (HR-HPV) and low-risk (LR-HPV) genotypes ( Refs 2,3,12). In particular, 15 HPV genotypes have been characterised as high-risk (HPV16, 18,31,33,35,39,45,51,52,56,58,59, 68, 73 and 82) (Ref. 14).…”
Section: Introductionmentioning
confidence: 99%